Pathogenicity of Beauveria bassiana strains isolated from Ostrinia nubilalis Hbn. (Lepidoptera: Pyralidae) to original host and to ladybirds (Coleoptera: Coccinelidae) - Ľudovít Cagáň; Vladimír Uhlík (Plant Protection Science, 1999)
B. bassiana strains isolated from 0. nubilalis were tested against the larvae of 0. nubilalis and coccinellid beetles in laboratory conditions (25°C). The first dead 0. nubilalis larvae were observed 48 hours after the application. During the first five days after the application, the efficiency of spore suspension was significantly higher than the efficiency of dry spore formulation. Spore suspension killed more than 50% of larvae after 72, or 96 hours. After dry spore formulation was used, more than 50% of larvae were killed during 96, or 120 hours. B. bassiana killed 50% of coccinellid larvae during 48 hours. After anot her 24 hours 83.3% (strain SK78), or 100% (strain SK99) coccinellid larvae were killed by fungus. More than 50% of dead adults of Coccinella septempunctata L. and Propylea quattuordecimptmctata (L.) was found 72-120 hours after application of fungus. This mea ns that B. bassiana was not adapted specifically to original host and killed effectively the adults and larvae of Coccinellidae. Different behaviour probably allows the coccinellids to escape from fungal infection in natural conditions